MODEL PEMBERDAYAAN PEREMPUAN BERBASIS KEBUTUHAN STRATEGIS GENDER - Linda Dwi Eriyanti (Jurnal Paradigma (JP), 2017)
This qualitative research is describes the strategic gender needs in the community PTPN XII Kebun Silosanen worker.  While the specific purpose of this research is to find a model of women's empowerment based strategic gender needs. The location chosen for this is Silosanen coffee plantations managed by PTPN XII Silo Jember, citing the quiet absorption of labor in plantations is quite large, reaching 1479 people. Data collection methods used were interviews, observation, literature, documentation studies and focus group discussion.